A high efficiency synchronous buck converter with adaptive dead-time control - Zhou, Mi (2021)
An adaptive inverter-based dead-time controller for synchronous DC-DC converter is proposed. With this controller, the switching time is precisely controlled and thus simultaneously eliminates the power losses caused by body-diode conduction, power-stage shoot-through current and inductor reverse current. A pair of inverters are used to replace the high speed comparators in this controller for even faster comparison. In addition, the proposed two-step (coarse and fine tuning) dynamic delay generator in this controller helps to achieve more accurate switching time with wider dead-time correction range. The controller can be incorporated into different converter topologies with a wide load range. In this paper, a voltage-mode buck converter with the proposed adaptive dead-time controller has been designed using 0.18 μm CMOS process. Simulation results show precisely controlled switching time under different loading conditions, and a 96% peak conversion efficiency can be achieved with the proposed technique.